A study on resources of Pseudotaxus chienii (Cheng) Cheng - HU Shao-qing; CHEN Zheng-hai; SHUN Meng-jun (浙江大学学报. 农业与生命科学版)
To make a thorough investigation of Pseudotaxus chienii (Cheng) Cheng in Zhejiang Province, distribution amount, habitat of this plant and the flora and community features of areas where they grow were studied, which was based on the principle of typical sampling. Our results showed that there were 11 distributive populations in Zhejiang. According to analysis on data from 29 quadrates, the total resources of P. chienii amount to 242.2 thousand clumps, the distributive area cover 408.08 hm2 and the community-types are comprised of 4 vegetative types, 8 formation groups and 11 formations. It is also shown that the flora of the communities of P. chienii is of ancient origin associated with complex geographical elements and characterized by some conspicuons transient features. Habitats of P. chienii has been found to be closely related to its ecological environments and its accompanying species Rhododendron simiarum.